Development of the Technical Pedagogical System to Enhance the Scale and Quality of Vocational Training Staff in Vietnam - Nguyễn Viết Sự (Journal of Technical Education Science, 2006)
At present, there are two universities, three colleges, 7 technical pedagogical departments of universities, of technical colleges and some classes of the ministries and branches which need a technical teachers training. The technical pedagogical system has been coping with many diffi culties which are not easy to tackle. This status needs to be innovated and developed strongly in order to meet the training need on technical teachers for technical and secondary schools, multi-technical and vocational centers and the upper secondary schools which are offering subjects on technology and job orientation. This writing proposes the orientation and solutions for development of the technical pedagogical system in the circumstance of commodity economy operated by market mechanism, with the socialist orientation, in the tendency of globalization and integration, in the process of implementing industrialization and modernization in our country in the next decade.